Ayurvedic management of Mental Depression - Acharya, Shripathi; Acharya, Rajeshwari (International Research Journal of Ayurveda & Yoga, 2020)
Depression is a common illness worldwide with more than 264 million people affected. It can cause the affected person to suffer greatly and function poorly. Mental depression is becoming common in Indi an population. Number of suicides are increasing day by day due to mental depression in modern India . Due to poverty, socioeconomic failure, insomnia , and mental conflicts , the incidence of mental depression has raised. Marriage clashes, economic burden , alcoholism , and mental stress are seen in these patients . In Ayurveda Manas is considered as one of the Tridannda of life . Ayurveda defines good health when the person is physically and mentally strong. There is detaild description about the various Manasik bhavas and Manas vyadhis. Scattered references of mental depression are found in various Ayurvedic classics. Mental depression can be correlated with the clinical condition under vishada, avasada, manodhukhaja unmada and kaphaja unmada. Various Ayurvedic treatments, yoga and pranayama, shows promising and effective results against mental depression. Shirodhara, Tailabhyanga, Sarvanga sweda, Nasya, Matrabasti yapana basti, Vipassana yoga, pranayama , dietatics , pathyapathya prayoga and Adravyabhoota chikitsa plays important role in the management of these patients .The present paper highlights the role of Ayurveda treatment in mental depression .